The Development of Flexible Scintillation Panels Based on Chalcogenide and Oxide Phosphors for Advanced X-Ray Scanners and Tomographs - Galkin, S.M.; Rybalka, I.A.; Tupitsyna І.А.; Zvereva, V.S.; Litichevskiy, V.A. (Science and Innovation, 2024)
The technology of flexible panels and dispersed scintillation elements for X-rays registration with high uniformity of scintillation parameters (mean deviation no more than 2%) and low cost has been developed. Parameters of flexible scintillation panels have been optimized, which enable their obtaining with high spatial resolution. The panels can be used as intensifying screens in medical and industrial radiography. Options for the operation of dual energy X-ray detectors working effectively in X-ray energy band (from 20 to 100 keV) have been proposed. Their possible applications are multienergy scanners and medical computer tomography.